Habitus i skiftande former: Ett begrepp och hur det används i tre svenska litteraturvetenskapliga undersökningar - Malmio, Kristina (Tidskrift för litteraturvetenskap, 2015)
Definitions of the Concept ’Habitus’, and its Uses in Three Swedish Literary Studies This article details a number of the various definitions of the concept of ’habitus’ and explores how the concept has been utilised in the analysis of authors and literature. Habitus is one of the key concepts of the theory of fields put forward by the French sociologist Pierre Bourdieu. Bourdieu has offered several more or less complex explanations of ’ habitus’, and scholars who have used the term have developed new interpretations and understand the concept in a number of varied ways. Therefore, it is my aim to offer and discuss various definitions in order to endow the concept with clarity. To this end, the following questions are of central interest to this study: how is ’habitus’ defined? In which contexts is it used? What do scholars strive to grasp by using the concept? After discussing the various definitions, I take a closer look at Les règles de l’art (1992) in order to see how Bourdieu employs the concept. I also study the use of ’habitus’ in three Swedish literary sociological studies, Eric Peurell’s A Writer’s Trajectory. Jan Fridegård in the Literary Field (1998), Petra Söderlund’s Romanticism and Reason. V.F. Palmblad’s Publishing House 1810‒1830 (2000) and David Gedin’s Masters of the Field. The Development of a Modern Writer’s Identity. 1880s (2004). My study shows that there is a sliding scale of understandings of the concept with no single common uniting feature and no general consensus of the absolute, necessary element of ’ habitus’. The most complex definitions of the concept are too complicated to be used in analysis, while the more simple definitions are only partly able to grasp the phenomena Bourdieu strives to unite in the concept of ’habitus’. I argue that ’habitus’ is most useful in the analysis of hidden class structures in society, understood then as ’embodied class’.